Desenvolvimento de um sistema construtivo de casas tipo térreo mais um pavimento com painéis pré-fabricados de concreto e blocos cerâmicos - Dias Júnior, José Graciano (2013)
The housing deficit in Brazil, according to the Ministry of Cities, is more than 5 million units, exceeding 14% of the total number of households. To supply this demand for housing, is currently seeking new systems and construction techniques that may produce residential units on an industrial scale. The building system called Olé Casas, developed in Ceará Brazil, has a high rate of production and manufactures residential units with prefabricated mixed cross section of ceramic bricks, concrete and mortar walls. This technology allows the construction of gasket and structure subsystems in a two-day interval with hand labor less specialized, reduced material waste and great cultural acceptance in the region. The construction system allows the construction of only one-story house and had not been assessed in accordance with the requirements laid out in Guideline SINAT No. 002, necessary prerequisite for the validation of the system to the Ministry of Cities of the Brazilian Federal Government. This work contain the main evaluations for buildings established in this Guideline by means of laboratory tests, field tests, and assessments in prototype, concluding that the building system meets the requirements set. Then, from the analysis of performance obtained and design guidelines, we proposed a model of two floor building using technology Olé Casas detailing its subsystems. For this proposed building, we analyzed the structural performance and concluded that the model meets the structural requirements supporting future studies with the use of technology to structural buildings with multiple floors.